4
$\begingroup$

The answer is (I think) $x^{\sqrt{x}-0.5} (1+0.5\ln(x))$, but how?

$\endgroup$
  • 5
    $\begingroup$ Hint: See if you can follow this one Derivative of $x^{x}$. Can you emulate it? $\endgroup$ – Amzoti Dec 19 '12 at 21:05
  • 2
    $\begingroup$ Hint: Write $x^{x^{1/2}} = e^{\ln(x)\cdot x^{1/2}}$ $\endgroup$ – andybenji Dec 20 '12 at 2:55
18
$\begingroup$

The way to differentiate most expressions of the form $x^{f(x)}$ is to rewrite them as $e^{f(x)\ln(x)},$ and then use the chain and product rules, and that works in this case too.

$\endgroup$
4
$\begingroup$

I'll probably get stones thrown at me for suggesting this, but let's view $x^{f(x)}$ as a hybrid of a power function $x^k$ and a composite exponential function $b^{f(x)}$. It's actually legitimate to take derivatives of these two simpler functions and add them together to get the derivative. $$\begin{align}\frac{d}{dx}x^{f(x)}&=\overbrace{f(x)x^{f(x)-1}}^{\text{power rule}}+\overbrace{x^{f(x)}\ln(x)}^{\text{exponential rule}}\cdot\overbrace{f'(x)}^{\text{chain rule}}\\ &=x^{f(x)} \left(\frac{f(x)}{x}+\ln(x)f'(x)\right)\end{align}$$ which is completely consistent with the "correct" approach of rewriting the function as $e^{f(x)\ln(x)}$ and using the chain and product rules. I don't recommend that you think this way, I just find this curious. I'd love to see a rigorous explanation for this happy coincidence that does not essentially appeal to rewriting as $e^{f(x)\ln(x)}$.


I think I found one. Let $F(y,z)=y^z$ with $y=g(x)$ and $z=f(x)$, then actually $F(y(x),z(x))=g(x)^{f(x)}$. Now using the chain rule for multivariate functions, $$\begin{align}\frac{d}{dx}g(x)^{f(x)}=\frac{dF}{dx}&=\frac{\partial F}{\partial y}\frac{dy}{dx}+\frac{\partial F}{\partial z}\frac{dz}{dx}\\&=zy^{z-1}\frac{dy}{dx}+y^z\ln(y)\frac{dz}{dx}\\&=f(x)(g(x))^{f(x)-1}g'(x)+g(x)^{f(x)}\ln(g(x))f'(x)\\&=g(x)^{f(x)}\left(\frac{f(x)g'(x)}{g(x)}+\ln(g(x))f'(x)\right)\end{align}$$

$\endgroup$
3
$\begingroup$

Let's write $E'$ to mean the derivative of the expression $E$.

Then in general: $$\begin{align} u^v & = e^{v\log u} \\ (u^v)' &= \left(e^{v\log u}\right)'\\ &=e^{v\log u}\cdot (v\log u)'\\ &=u^v \left(v'\log u + v\frac {u'}u\right) \\ &=u^vv'\log u + u^{v-1}vu' \end{align}$$

To check, try taking one of $u$ or $v$ to be the identity function and the other to be a constant.

$\endgroup$
2
$\begingroup$

$$y=x^{\sqrt{x}}$$ $$\ln y=\sqrt{x}\ln x$$ now differentiate w.r.t. x using chain rule $$\dfrac {1}{y}\cdot\dfrac {dy}{dx}=\dfrac{\sqrt{x}}{x}+\dfrac{\ln x}{2\sqrt x}$$ $$\dfrac {dy}{dx}=x^{\sqrt{x}}\cdot\left(\dfrac{2+\ln x}{2\sqrt x}\right)$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.